Comparison of total intravenous anesthesia and sevoflurane-fentanyl anesthesia for outpatient otorhinolaryngeal surgery (2002)
Study Objective: To compare the recovery characteristics of two widely used anesthetic techniques: remifentanyl-propofol and sevoflurane-fentanyl in a standardized ambulatory population. Design: Randomized, single-blinded study. Setting: University-affiliated medical center. Patients: 50 ASA physical status I and II patients undergoing elective ambulatory otorhinolaryngeal surgery. Interventions: Patients were randomized two groups to receive total intravenous anesthesia (TIVA group) with remifentanil and propofol or sevoflurane-fentanyl (SF group). TIVA patients received induction with propofol 1.5 mg/kg intravenously (IV) and remifentanil 0.5 ?/kg IV. The anesthesia was continued with a continuous infusion of propofol 100 ?g/kg/min and remifentanil 0.0625-0.25 ?g/kg/min. The SF group received, at induction, fentanyl 2 ?g/kg followed by propofol 1.5 mg/kg IV. Maintenance was obtained with 1 to 1.5 minimum alveolar concentration of sevoflurane and bolus of fentanyl 1 ?g/kg IV as needed. Measurements and Main Results: Early recovery times (eye opening, response to commands, extubation, orientation, operating room stay after surgery, and Aldrete score ?9) and patient satisfaction were similar between the two groups. Postanesthetic discharge scoring system (PADSS) ? 9 was significantly shorter for the TIVA group (135.9 ± 51 vs. 103 ± 32 min) (p less than 0.01) but this difference was not associated with a shorter postanesthesia care unit (PACU) length of stay. Conclusion: Early recovery times are comparable between total intravenous anesthesia and sevoflurane-based anesthesia. Even though patients in the TIVA group achieved home readiness criteria in a significantly shorter time, this technique does not shorten PACU length of stay, which depends instead on multiple nonmedical and administrative issues. © 2002 by Elsevier Science Inc.